Cofactor-independent RNA editing by a synthetic S-type PPR protein. Issue 1 (23rd December 2021) - Bernath-Levin, Kalia; Schmidberger, Jason; Honkanen, Suvi; Gutmann, Bernard; Sun, Yueming Kelly; Pullakhandam, Anuradha; Colas des Francs-Small, Catherine; Bond, Charles S; Small, Ian
Abstract: Pentatricopeptide repeat (PPR) proteins are RNA-binding proteins that are attractive tools for RNA processing in synthetic biology applications given their modular structure and ease of design. Several distinct types of motifs have been described from natural PPR proteins, but almost all work so far with synthetic PPR proteins has focused on the most widespread P-type motifs. We have investigated synthetic PPR proteins based on tandem repeats of the more compact S-type PPR motif found in plant organellar RNA editing factors and particularly prevalent in the lycophyte Selaginella . With the aid of a novel plate-based screening method, we show that synthetic S-type PPR proteins are easy to design and bind with high affinity and specificity and are functional in a wide range of pH, salt and temperature conditions. We find that they outperform a synthetic P-type PPR scaffold in many situations. We designed an S-type editing factor to edit an RNA target in E. coli and demonstrate that it edits effectively without requiring any additional cofactors to be added to the system. These qualities make S-type PPR scaffolds ideal for developing new RNA processing tools.